Low temperature processing of doped indium oxide thin films for electronic applications - Alves, André Frutuoso (2023)
Transparent conducting oxides (TCOs) are critical components in the operation of sev-eral optoelectronic devices as well as transparent electronics. One of the most widely used, indium tin oxide (ITO), requires very expensive equipment and controlled conditions to be deposited. Solution combustion synthesis (SCS) is a simple and low-cost method being stud-ied to produce the same oxides. Thin films of indium oxide doped with hafnium produced by SCS have already shown very promising properties when annealed at 400 °C. This work will study the viability of producing these same films at even lower temperatures, enough to en-able the use of flexible substrates. TCO thin films were produced at low temperature such as 200 °C by using an infrared (IR) oven instead of the typical hotplate annealing. A 0.5 M % Hf-doped In2O3 thin film annealed at 350 °C with an IR oven achieved the best properties with a bulk resistivity of 1.3 × 10-1 Ω·cm, mobility of 1.33 cm2/Vs, carrier concentration of 3.6 × 1019 cm-3. These results were even better when compared with high annealing temperatures. As proof of concept this TCO was successfully implemented in a liquid crystal cell and electro-chromic device showing their potential for real applications.